2020
DOI: 10.3389/fcell.2020.00762
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchidism and Testicular Tumor: Comprehensive Analysis of Common Clinical Features and Search of SNVs in the KIT and AR Genes

Abstract: Allelic variants in genes implicated in the development of testicular germ cell tumor (TGCT) could be present in patients with cryptorchidism (CO). Currently; the mechanisms explaining this relationship are still unknown. In this study the common clinical features in patients with CO and TGCT and 6 variants of KIT and AR genes associated to TGCT were analyzed. Population analyzed included 328 individuals: 91 patients with CO; 79 with TGCT, 13 of them with previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The clinical stage of both patients was T3a, and the age of diagnosis was 55 and 62. This variant was previously detected in the group with testicular cancer, but no significant difference was found compared to the control group [ 11 ]. It was known that the variants in the AR gene which plays a role in the development of prostate tissue were associated with an increased risk of PCa [ 12 ].…”
Section: Discussionmentioning
confidence: 89%
“…The clinical stage of both patients was T3a, and the age of diagnosis was 55 and 62. This variant was previously detected in the group with testicular cancer, but no significant difference was found compared to the control group [ 11 ]. It was known that the variants in the AR gene which plays a role in the development of prostate tissue were associated with an increased risk of PCa [ 12 ].…”
Section: Discussionmentioning
confidence: 89%
“…Later, all types of germ cell tumors (such as seminomas, yolk sac tumors, embryonal carcinomas, etc.) arise as well [6,26,38,72,73,[132][133][134][135][136][137][138][139]. As to our review, most of the gonads of patients with AIS were abdomino-pelvic (51 cases, 23%) [10,[12][13][14][15]21,24,26,[31][32][33]35,37,39,42,[44][45][46]48,49,[51][52][53][54][56][57][58][59]62,[65][66][67][68][69]71,83] or inguinal (18 cases, 8%) …”
Section: Discussionmentioning
confidence: 99%
“…When the proto-oncogene c-Kit is mutated, the Kit protein show an activated state without binding to the ligand SCF, thereby stimulating the continuous proliferation of tumor cells and inducing the uncontrolled anti-apoptotic signal, resulting in the cancerization [ 30 ]. It was reported that compared with normal testicular tissue, 88 % (22/25) of seminoma and 44.4 % (4/9) of non-seminoma expressed kit protein, of which 9 cases expressed kit protein seminoma detected c-kit gene mutation (40.9 %, 9/22) [ 31 ]. In addition, Cheng et al reported that among 22 patients with germ cell tumors, 6 cases (27 %) were detected with c-Kit gene point mutation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%